Pengaruh Debt to Equity Ratio, Total Assets Turnover, Firm Size, dan Current Ratio terhadap Return on Assets - Aurick Chandra; Felicia Wijaya; Angelia Angelia; Keumala Hayati (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This study aimed to examine and analyze the effects of the Debt to Equity Ratio (DER), Total Assets Turnover (TATO), firm size, and Current Ratio (CR) on Return on Assets (ROA) on the manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019 Research methodology: This research approach used quantitative research with descriptive research type. The research sample was determined by purposive sampling method to obtain 93 manufacturing companies listed on the Indonesia Stock exchange in 2017-2019. Results: The study results with simultaneous hypothesis testing showed that the Debt to Equity Ratio, Total Assets Turnover, firm size, and Current Ratio had a significant influence on the Return on Assets. Partial testing of the hypothesis showed that the Debt to Equity Ratio had a negative influence and significant on the Return on Assets. Total assets turnover and firm size had a positive influence and significance on the Return on Assets. However, the Current Ratio had no influence and was not significant on the Return on Assets. Limitations: The use of historical data and variables was limited, only three years and five variables. Contribution: This research can be used for adding knowledge in the financial field, especially for those who want to invest in a company by seeing the Return on Assets ratio. Keywords: Debt to Equity Ratio (DER), Total Assets Turnover (TATO), Firm Size, Current Ratio (CR), Return on Assets (ROA)